Income Distribution From Outward-Looking Development Policies (The Pakistan Development Review, 1974)
Income distribution has become a central concern in developing market economies, now that breakthroughs are being achieved in expanding output. Severe inequalities in the distribution of the benefits of development are practi¬cally universal and appear to be growing.1 Will these inequalities be reduced or cured by the outward-looking policies now being recommended to developing countries ? This paper analyses these policies and arrives at a generally negative answer. In most developing countries, inequalities cannot be expected to cure themselves under outward-looking policies, no matter how desirable these policies may be for other reasons.* Inequalities may even increase unless major efforts are made to redistribute income. The paper starts with a brief description of the policies now being recommended. There follow sections dealing with inequality-producing influences associated with this development strategy. These influences are discussed under the following headings: